Case report: Idiopathic pulmonary fibrosis induced by nab-paclitaxel: A rare complication - Shen, Jiahui; Wen, Zhongyong; Lin, Jingxia; Su, Huiwen (Frontiers in Pharmacology, 2023)
Background: Ovarian cancer is one of the deadliest gynecological cancers, with the most advanced disease and poor survival. Although BRCA genes play a key role in maintaining genomic stability and providing the possibility of clinically individualized treatments, with the emergence of new and more appropriate treatment options, new treatment–related adverse events are challenging and difficult for clinicians. Case presentation: An 80-year-old Chinese woman was diagnosed with stage IIIC ovarian high-grade serous adenocarcinoma (CT3cN1MX) with BRCA2 as the causative gene. She underwent three courses of neoadjuvant chemotherapy with nab-paclitaxel 400 mg and carboplatin 450 mg before surgery. Chest HRCT prior to chemotherapy demonstrated bilateral interstitial pneumonia. During chemotherapy, there were four episodes of dry cough, shortness of breath, dyspnea, and three episodes of bone marrow suppression. The symptoms became intermittent and progressively worse, and after three sessions of empirical cough and phlegm relief, oxygen inhalation, corticosteroids, anti-infectives, and leukopenia therapy, the symptoms became intermittent and progressively worse. The diagnosis of idiopathic pulmonary fibrosis came a week after the third round of chemotherapy. After a strong dose of corticosteroids and nintedanib anti-fibrosis therapy, the pulmonary symptoms abated, and intermediate tumor starvation was performed. The combination therapy was subsequently discontinued, and the patient experienced significant relief from pulmonary symptoms. Treatment response was positive following single-agent nab-paclitaxel 400 mg chemotherapy in combination with nintedanib 150 mg anti-fibrosis therapy. Conclusion: In this report, we describe a rare case of idiopathic pulmonary fibrosis associated with the use of nab-paclitaxel and carboplatin in ovarian cancer. During treatment, it is necessary to maintain a high level of vigilance for patients with interstitial pneumonia and engage the attention of clinicians to improve medication safety. Early diagnosis and anti-fibrosis therapy can reverse lung damage.